Implementasi Habituasi Profil Pelajar Pancasila dalam Pembentukan Karakter Siswa: Faktor Pendukung dan Penghambat - Widyawati Wahyu Ningsih; Nina Sofiana; Hamidaturrohmah Hamidaturrohmah (Edukhasi: Jurnal Inovasi Pendidikan, 2023)
This study aims to analyze the implementation of Pancasila student profile habituation in the formation of students' character as well as the supporting and inhibiting factors in its implementation. The type of research used in this research is descriptive qualitative. The subjects of this study were students and teachers of grades 1 and 4 at SDN 3 Ngasem, Tahunan Jepara. Data collection methods used are observation, interviews and documentation. The results of the study show that the implementation of the independent curriculum at SDN 3 Ngasem in grades 1 and 4 has been well implemented. The 6 elements of Pancasila student profile habituation have also been implemented in the learning process by having a special program. Factors supporting the implementation of habituation of the Pancasila student profile are the self-determination of students, educators, parents, and the school and home environment. The inhibiting factors of this habituation are the teacher's lack of understanding of the independent curriculum, moral degradation in students, minimal learning substance and the lack of role of parents of students in supporting this habituation at home. The solution to overcoming obstacles to the implementation of Pancasila student profile habituation is that educators are expected to attend seminars or collaborate in using the independent curriculum, students are given more activities that lead to habituation of Pancasila student profiles, and invite parents to collaborate in instilling Pancasila student profile habituation at school